2022 IEEE International Instrumentation and Measurement Technology Conference (I2MTC) 2022
DOI: 10.1109/i2mtc48687.2022.9806699
|View full text |Cite
|
Sign up to set email alerts
|

Convolutional Neural Network Aided Chemical Species Tomography for Dynamic Temperature Imaging

Abstract: Chemical Species Tomography (CST) using Tunable Diode Laser Absorption Spectroscopy (TDLAS) is an in-situ technique to reconstruct the two-dimensional temperature distributions in combustion diagnosis. However, limited by the lack of projection data, traditionally computational tomographic algorithms are inherently rankdeficient, causing artefacts and severe uncertainty in the retrieved images. Recently, data-driven approaches, such as deep learning algorithms, have been validated to be more accurate and stabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Nonetheless, several studies have successfully applied neural networks to regression of absorption spectra and reported precision increases compared to conventional approaches [8][9][10][11]. In our recent study we observed good performance of a neural network based noise reduction scheme for a specific noise structure where all tested conventional methods fell short [12].…”
Section: Introductionmentioning
confidence: 59%
“…Nonetheless, several studies have successfully applied neural networks to regression of absorption spectra and reported precision increases compared to conventional approaches [8][9][10][11]. In our recent study we observed good performance of a neural network based noise reduction scheme for a specific noise structure where all tested conventional methods fell short [12].…”
Section: Introductionmentioning
confidence: 59%